Potent O-antigen-deficient (rough) mutants of Salmonella Typhimurium secreting Lawsonia intracellularis antigens enhance immunogenicity and provide single-immunization protection against proliferative enteropathy and salmonellosis in a murine model - Suyeon Park; Gayeon Won; Jehyoung Kim; Hyeun Bum Kim; John Hwa Lee (Veterinary Research, 2018)
Abstract The obligate intracellular pathogen Lawsonia intracellularis (LI), the etiological agent of proliferative enteropathy (PE), poses a substantial economic loss in the swine industry worldwide. In this study, we genetically engineered an O-antigen-deficient (rough) Salmonella strain secreting four selected immunogenic LI antigens, namely OptA, OptB, LfliC, and Lhly. The genes encoding these antigens were individually inserted in the expression vector plasmid pJHL65, and the resultant plasmids were transformed into the ∆asd ∆lon ∆cpxR ∆rfaL Salmonella Typhimurium (ST) strain JOL1800. The individual expression of the selected LI antigens in JOL1800 was validated by an immunoblotting assay. We observed significant (P < 0.05) induction of systemic IgG and mucosal IgA responses against each LI antigen or Salmonella outer membrane protein in mice immunized once orally with a mixture of four JOL1800-derived strains. Further, mRNA of IL-4 and IFN-γ were highly upregulated in splenic T cells re-stimulated in vitro with individual purified antigens. Subsequently, immunized mice showed significant protection against challenge with 106.9 TCID50 LI or 2 × 109 CFU of a virulent ST strain. At day 8 post-challenge, no mice in the immunized groups showed the presence of LI-specific genomic DNA (gDNA) in stool samples, while 50% of non-immunized mice were positive for LI-specific gDNA. Further, all the immunized mice survived the virulent ST challenge, compared to a 20% mortality rate observed in the control mice. Collectively, the constructed rough ST-based LI vaccine candidate efficiently elicited LI and ST-specific humoral and cell-mediated immunity and conferred proper dual protection against PE and salmonellosis.